2008
DOI: 10.1038/nrc2400
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the biological roles of PAI2 (SERPINB2) in cancer

Abstract: Tumour expression of the urokinase plasminogen activator correlates with invasive capacity. Consequently, inhibition of this serine protease by physiological inhibitors should decrease invasion and metastasis. However, of the two main urokinase inhibitors, high tumour levels of the type 1 inhibitor actually promote tumour progression, whereas high levels of the type 2 inhibitor decrease tumour growth and metastasis. We propose that the basis of this apparently paradoxical action of two similar serine protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(226 citation statements)
references
References 150 publications
7
218
1
Order By: Relevance
“…Reduced expression of TSP-1 is an important component of the angiogenic switch, and decrease in its expression facilitates growth of several tumor types, including bladder, breast, and ovarian cancer, fibrosarcoma, and glioblastoma (18,19,22). PAI-2 is one of the two major physiological inhibitors of urokinase plasminogen activator, which has been shown to promote invasion and metastasis in various cancer types (20). Strikingly, a number of studies indicated that higher PAI-2 expression in tumors is linked with prolonged survival, decreased metastasis or decreased tumor size (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced expression of TSP-1 is an important component of the angiogenic switch, and decrease in its expression facilitates growth of several tumor types, including bladder, breast, and ovarian cancer, fibrosarcoma, and glioblastoma (18,19,22). PAI-2 is one of the two major physiological inhibitors of urokinase plasminogen activator, which has been shown to promote invasion and metastasis in various cancer types (20). Strikingly, a number of studies indicated that higher PAI-2 expression in tumors is linked with prolonged survival, decreased metastasis or decreased tumor size (20).…”
Section: Discussionmentioning
confidence: 99%
“…PAI-2 is one of the two major physiological inhibitors of urokinase plasminogen activator, which has been shown to promote invasion and metastasis in various cancer types (20). Strikingly, a number of studies indicated that higher PAI-2 expression in tumors is linked with prolonged survival, decreased metastasis or decreased tumor size (20). Because access to vasculature is a critical component to metastasis, kinases that increase the angiogenic potential of tumor cells would be expected to increase their metastatic potential as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…103 Preclinical and translational advances. Within the abundant preclinical literature that has been published during the last 13 months on ICD-inducing chemotherapeutics, we found of particular interest the works of: (1) Pallasch and colleagues (Massachusetts Institute of Technology; Cambridge, MA, US), who demonstrated that cyclophosphamide induces an acute secretory phenotype in malignant cells, stimulating the release of various immunostimulatory cytokines that promotes a macrophagedriven, tumor-targeting innate immune response; [104][105][106] (2) Tavora and collaborators (Barts Cancer Institute; London, UK), who showed that the inhibition of protein tyrosine kinase 2 (PTK2, also known as FAK) [107][108][109] in the endothelial tumor [130][131][132][133] in the establishment of a collagenenriched tumor microenvironment contributing to the resistance of (at least a subset of) breast carcinomas to doxorubicin. 134 Recently initiated clinical trials.…”
Section: Update On the Development Of Icd-inducing Chemotherapeuticsmentioning
confidence: 99%
“…Consequently, uPA and SerpinE1 expression is recommended as an independent prognostic indicator in node-negative breast cancer (9). On the contrary, tumor expression of SerpinB2 is correlated with increased relapse-free survival in breast cancer (and possibly other cancer types) (10). Further, the relationship between outcome and high SerpinB2 levels in node-negative breast cancer is only relevant if uPA levels are also elevated (1,11), suggesting that the inhibitory relationship between uPA and SerpinB2 mediates this functionality.…”
mentioning
confidence: 99%